Tiere – Texte – Transformationen: Kritische Perspektiven der Human-Animal Studies - Kompatscher, Gabriela; Schachinger, Karin; Spannring, Reingard; Boucabeille, Alejandro; Heuberger, Reinhard; Oberprantacher, Andreas (transcript, 2015)
This volume aims to encourage subjecting post-humanist transformations to experiments both in thought and in practice. It combines new empirical and theoretical work by international authors in the research field of human-animal studies: along with examples of how the relationship between animals and humans was handled in the past and how it is presented and discussed in contemporary art and science, this volume also contains analyses of literary and philosophical texts and linguistic research. Other contributions provide information on the observable and potential social, scientific, and economic shifts in the relationship between humans and animals.